Antecedents, Processes, and Outcomes of Sustainable Professional Empowerment of Women Based on ICT in Digital Era - Mehdi Mohammadi; Farzane Deimehkar Haghighi (مطالعات اجتماعی روان‌شناختی زنان)
Women's empowerment in all dimensions is essential for achieving comprehensive sustainable development. This research aimed to provide a model in the field of professional empowerment of women using (ICT). In this context, by using a qualitative research approach and the meta-synthesis method, studies related to the topic were identified and evaluated. A total of 74 studies were selected and analyzed for use in the research. The research findings were presented in three axes of Antecedents in political, social, economic, and cultural-educational roles of international organizations, governments, and families in empowering women, Processes by Emphasis on developing women's individual capabilities, increasing their political, social, and economic participation, and focusing on women's leadership and management in the digital age and Outcomes in Sustainable development, individual and social development, economic and political development using ICT. Results showed that women's empowerment through ICT is essential for achieving sustainable development. This research provides a roadmap for policymakers, practitioners, and researchers to develop and implement effective interventions in this area.